Gender Interpretation Based on Artificial Intelligence: Between Chat GPT and Meta AI - Ilafi, Balqis Sakhaa; Nurrohim, Ahmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Currently, gender issues have become one of the most widely discussed topics across various groups. In this context, the research conducted will focus on issues related to verses that are considered to contain gender bias. On the other hand, Artificial Intelligence (AI) is increasingly popular in various aspects of life. This technology has become a reliable tool, particularly among young Muslim generations and modern society, and is often used as a primary reference, including in addressing religious matters. This study aims to examine the perspective of gender interpretation by utilizing AI as an auxiliary tool. AI will be used to identify gender bias through the analysis of linguistic patterns found in interpretations. The research focuses on gender bias in the interpretation of Quranic verses, specifically QS. An-Nisa: 34, QS. Al-Baqarah: 228, QS. Al-Baqarah: 282, QS. An-Nisa: 7, and QS. Al-Baqarah: 223. Gender biases that frequently appear in traditional interpretations are often rooted in patriarchal culture, which reinforces gender hierarchies. Such interpretations tend to position men as dominant in various aspects of life, such as household leadership, legal testimony, and inheritance distribution. This study employs a qualitative approach based on library research to analyze both traditional and contemporary interpretations while integrating artificial intelligence (AI) as a supporting tool. The findings indicate that contemporary approaches offer more equitable and inclusive perspectives by understanding Quranic verses within their historical context. For instance, the term qawwāmūna in QS. An-Nisa: 34 is interpreted not as the absolute superiority of men but as an economic responsibility assigned to them. AI also proves effective in supporting the development of interpretations that are relevant to modern social challenges. By combining traditional and contemporary approaches with modern technology such as AI, this study is expected to renew the understanding of Quranic verses, reflecting values of justice, equality, and inclusivity. This research makes a significant contribution to the discourse on gender interpretation by bridging classical and modern methodologies while addressing the needs of contemporary Muslim communities.